2023
DOI: 10.1093/jxb/erad088
|View full text |Cite
|
Sign up to set email alerts
|

LONG HYPOCOTYL IN FAR-RED 1 mediates a trade-off between growth and defence under shade in Arabidopsis

Abstract: Plants respond to vegetative shade with developmental and physiological changes that is collectively known as shade avoidance syndrome (SAS). Although LONG HYPOCOTYL IN FAR-RED 1 (HFR1) is known to be a negative regulator of SAS by forming heterodimers with other basic helix-loop-helix (bHLH) transcription factors to inhibit them, its function in genome-wide transcriptional regulation is not fully elucidated. Here, we performed RNA-sequencing analyses of hfr1-5 and HFR1 overexpression line (HFR1(ΔN)-OE) to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The shade and the invasion of insects or microbes usually jointly affect plant survival, therefore, plants need to balance the interactions between shade avoidance and defense responses to achieve a better survival [128,129]. PIFs have been revealed to be involved in this interaction by modulating resource allocation to coordinate plant defense and development [130,131]. It is reported that when shaded plants are challenged with pathogens or herbivores, growth is prioritized over defense responses [130][131][132][133].…”
Section: Role Of Pifs In Biotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The shade and the invasion of insects or microbes usually jointly affect plant survival, therefore, plants need to balance the interactions between shade avoidance and defense responses to achieve a better survival [128,129]. PIFs have been revealed to be involved in this interaction by modulating resource allocation to coordinate plant defense and development [130,131]. It is reported that when shaded plants are challenged with pathogens or herbivores, growth is prioritized over defense responses [130][131][132][133].…”
Section: Role Of Pifs In Biotic Stressmentioning
confidence: 99%
“…PIFs have been revealed to be involved in this interaction by modulating resource allocation to coordinate plant defense and development [130,131]. It is reported that when shaded plants are challenged with pathogens or herbivores, growth is prioritized over defense responses [130][131][132][133]. Specifically, under the concurrence of pest infestation and shading, PIF4 suppresses the JA signaling pathway by repressing the transcription of Myelocytomatosis (MYC), the master regulator in the pathway [130].…”
Section: Role Of Pifs In Biotic Stressmentioning
confidence: 99%
“…pifq and pqp6p7 ) have been widely used to study PIF functions (e.g. Jiang et al ., 2020 ; Bernula et al ., 2021 ; Yoo et al ., 2021 ; Piskurewicz et al ., 2023 ; Sng et al ., 2023 ). The identification of the hidden nia2‐2 mutation revealed here might render it worthwhile re‐examining the alternative interpretation that some of the reported mutant phenotypes were due to the deficiency in N metabolism and/or NO production, especially for any studies investigating the crosstalk between the PIF and NO signalling pathways (Lozano‐Juste & León, 2011 ; Bai et al ., 2014 ).…”
mentioning
confidence: 99%